2015
DOI: 10.3233/jrs-150693
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-oxidant properties: Is there a link?

Abstract: The effects of studied agents on the intensity of inflammation and lipid peroxidation were inconsistent. The results of the study did not show a clear link between anti-inflammatory and anti-oxidant activity. Further research in potential anti-inflammatory activity of new drugs exhibiting antioxidant properties needs to be done before recommending their use in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Forest environments have been shown to reduce stress and increase comfort, calm, and feelings of refreshment (Tsunetsugu et al, 2007). Other studies have identified phytoncides as the main beneficial factor in the forest environment (Nazaruk & Borzym-Kluczyk, 2015; Reenaers et al, 2016; Valeeva, Titarenko, Khaziakhmetova, & Ziganshina, 2015). These are naturally antibiotic, volatile substances emitted by trees and plants as a protective mechanism against harmful insects, animals, or microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forest environments have been shown to reduce stress and increase comfort, calm, and feelings of refreshment (Tsunetsugu et al, 2007). Other studies have identified phytoncides as the main beneficial factor in the forest environment (Nazaruk & Borzym-Kluczyk, 2015; Reenaers et al, 2016; Valeeva, Titarenko, Khaziakhmetova, & Ziganshina, 2015). These are naturally antibiotic, volatile substances emitted by trees and plants as a protective mechanism against harmful insects, animals, or microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…These are naturally antibiotic, volatile substances emitted by trees and plants as a protective mechanism against harmful insects, animals, or microorganisms. Phytoncides have antigastropathic, anti-inflammatory, and antioxidant activities (Nazaruk & Borzym-Kluczyk, 2015; Reenaers et al, 2016; Valeeva et al, 2015). Several studies have shown that they prevent stress-induced hypertension (Li et al, 2010; Li et al, 2011) and reduce cortisol levels and overall oxidative stress (Li et al, 2011; Mao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%